Flexible solar and thermal energy conversion devices: Organic photovoltaics (OPVs), organic thermoelectric generators (OTEGs) and hybrid PV-TEG systems - O'Shaughnessy, Seamus; Pakdel, Amir (My University, 2022)
Solar and thermal energy conversion are two major renewable energy technologies highly sought after in the past two decades by academia, industry, and policymakers. Besides the traditionally large-size solar and thermal energy convertors, more recently, lightweight, flexible solar cells and thermoelectric generators (TEGs) based on organic semiconductor materials have attracted much attention due to the booming development of wearable electronics. In this article, we comprehensively review the scientific advances in the field of organic photovoltaics and organic thermoelectric materials and devices, focusing both on the fundamental processes as well as the development of flexible devices. This review brings together state-of-the-art technological advancements in the field of hybrid photovoltaic-thermoelectric energy harvesters, with overarching relevance and implications for the development of self-powered wearable electronics for internet-of-things (IoT) applications.
PUBLISHED
Keywords: Organic semiconductors; Organic photovoltaics; Organic solar cells; Organic thermoelectrics; Hybrid PV-TEG; Wearable electronics